Distribution and phylogenetics of hepatitis E virus genotype 4 in humans and animals. (4th March 2022) - Li, Bingzhe; Wagner, Abram L.; Song, Yujian; Chen, Xiangxiang; Lu, Yihan
Abstract: Background: Worldwide, hepatitis E virus (HEV) infection is considered a significant public health concern. In particular, HEV genotype 4 (HEV‐4) has spread to more areas and host species. In this study, we describe the global distribution of HEV‐4 and characterize HEV‐4 subtypes by host, country and year of isolation. Methods: We retrospectively collected HEV‐4 sequences available before December 31, 2019, in GenBank. HEV‐4 and its subtypes were determined using phylogenetic comparison with HEV reference sequences. Information on the isolation of the sequences was extracted from the GenBank or original publications. Temporal, spatial and host characteristics of the sequences were summarized and nucleotide similarity was calculated based on five amplified fragments within HEV genome, stratified by host, country and year. Results: A total of 2295 HEV‐4 complete and partial nucleotide sequences were studied. The majority (92.7%) was isolated in China's mainland, Japan, Hong Kong and France. A total of 20 animal hosts were documented, though swine remained predominant (71.7%). Globally, prevalent HEV‐4 subtypes changed remarkably over the last 18 years. Subtypes 4a, 4b, 4d and 4h were most commonly isolated (80.3%). Subtypes 4c, 4e, 4f, 4g and 4i remained limited in temporal distribution. High nucleotide similarities were observed between the sequences amplified in HEV ORF2, in the same and neighbouring countries, and in similar animal hosts. Conclusion: China and Japan are endemic for HEV‐4, and have all the subtypes. In Europe, France has a high prevalence of HEV‐4. Increases in affected areas and animal hosts imply consistent cross‐border and cross‐species transmission.